Colonel Jan Breytenbach – Military Historian or Storyteller? An Analysis of Breytenbach’s Work using a Military History Conceptual Framework - Punt, Carl (Scientia Militaria - South African Journal of Military Studies, 2024)
Books on the South African Border War have flooded the popular market in the last two decades. Historians, journalists, and particularly ex-soldiers – often amateur writers – have tapped into the market. The genres of books include, but are not limited to, personal accounts, autobiographies, regimental histories, journalist accounts, and academic books. Jan Breytenbach was one of the first South African Defence Force officers to write about the Border War. He published seven books, and paved the way for many writers to follow in his footsteps. Most of his books focus on the history of 32 Battalion. Against this background, the study on which this article is based, aimed to analyse Breytenbach’s writing using a conceptual framework put forward by military historians.